Seeds and peels – from by-products to potentially commercial antioxidants towards industrial biotechnology - Senawi, Norshazila; Ruzian, Nurliyana; Koya, Mustapha Suleiman; Syed Osman Idid, Syed Zahir Idid; Mohamed Rehan, Aisyah; Khan Chowdhury, Ahmed Jalal; Kamarudin, Kamarul Rahim (2012)
The seeds of guava, papaya and mango were tested for their antioxidant levels and activities (i.e the primary and the secondary antioxidant activities. The antioxidant levels and activities in pulps and seeds of two species of dragon fruits, Hylocereus undatus (white dragon fruit) and Hylocereus polyrhizus (red dragon fruit) were tested and compared with each other in order to investigate the possibilities of utilising the selected fruit seeds and peels as commercial nutraceuticals in the future.